Biotic and abiotic processes in Ediacaran spheroid formation - Cañadas, Fuencisla; Papineau, Dominic; She, Zhenbing (Frontiers in Earth Science, 2024)
Organic-rich shales from the uppermost Doushantuo Fm. (South China) record one of the most negative carbonate carbon isotopic excursions in Earth's history, known as the Shuram excursion, and contain meter to micro-size spheroids. In this study, we use Raman and energy dispersive spectroscopy to identify and describe the most common diagenetic spheroids to refine our understanding of the profound perturbations of the carbon cycle and the evolution of pore fluid chemistry imprinted in the sedimentary Precambrian record, especially in the late Ediacaran. The presence of 13 C-depleted carbonate concretions or organic matter (OM) enclosed by lenticular dolomitic structures within the host shale unit suggests OM remineralisation and anaerobic oxidation, resulting in authigenic carbonate precipitation during the earliest stages of sediment diagenesis. Other mineralogical features, however, point to high levels of primary production, such as apatite bands that host spheroidal microfossils with highly fluorescent quartz and OM within abiotic concretions. These observations highlight the importance of considering co-occurring biotic and abiotic processes in explaining the formation of diagenetic spheroids in ancient sedimentary environments. From an astrobiology perspective, the interplay of biotic and abiotic processes reflects the complexity of early life systems and the environments that may exist on other terrestrial planets. Understanding the signatures of biotic and abiotic interactions in the Doushantuo Fm. is crucial for identifying potential biosignatures in extraterrestrial materials, thereby enhancing our understanding of life's universality and adaptability in diverse and extreme environments.